Nonviolent Theology in the Syrian Protests: A Critical Analysis of Jawdat Sa‘īd's Qur'anic Exegesis - Rudiger Lohlker (UIN Sunan Gunung Djati Bandung, 2024)
The non-violent protests in Syria against the government, before eventually being co-opted by armed forces, marked a unique resistance against the regime during that period. Jawdat Sa‘īd, a theorist, writer, and activist, inspired activists during this time by advocating for a theology of non-violence as the authentic foundation for Islamic life. The theological basis was drawn from a specific interpretation of the Quran. Sa‘īd's understanding of the Quranic revelation was analysed using the approach formulated by Shahab Ahmed, demonstrating its validity in comprehending Islamic thought deeply. The research problem addressed the non-violent characteristics of the Syrian protests, while the research goal aimed to unveil the critical role of Sa‘īd's interpretation of the Quran in shaping this movement. Through methods involving text analysis and Sa‘īd's understanding of specific verses, the research findings highlighted the impact of Sa‘īd's non-violent theology on activists and the foundation for peaceful resistance. The research conclusion emphasised the importance of contextual understanding of the Quran and a non-violent perspective in shaping social movements. This study contributes to a better understanding of contemporary Islamic thought and strategies for resistance that can be adopted in similar contexts.